Effectiveness of Classical Music Therapy on Decreasing the Level of Auditory Hallucinations in Schizophrenia Patients: A Literature Review - Ridho, Fiki Muhammad (Faculty of Medicine, Universitas Airlangga, 2023)
Introduction: Hallucinations are one of the symptoms most often experienced by schizophrenia patients. Auditory hallucinations affect about 70% of schizophrenia patients who experience hallucinations. Classical music therapy is one of the non-pharmacological interventions that can be done. Music can be used as a non-pharmacological therapy option because it can improve, restore and maintain physical, mental, emotional, social and spiritual health. Objective: This study aims to further discuss the effectiveness of classical music therapy in reducing the level of auditory hallucinations in schizophrenia patients. Methods: This study uses the literature review method by searching research data on Google Scholar database. Result: Based on the result of the data search, 8 journals were studied in this study. Discussion: The result found in 8 journals stated that classical music therapy as a non-pharmacological therapy can reduce the intensity of auditory hallucinations in schizophrenia patients. Classical music can evoke changes at the level of important neuromodulators such as dopamine, endorphins, endogenous cannabinoids and nitric oxide. So that the administration of classical music theraoy can eliminate the neurotransmitters of depression, stress, anxiety, and can suppress the symptoms of hallucinations including auditory hallucinations. Conclusion: This study concluded that classical music therapy is effective in reducing the level of auditory hallucinations in schizophrenia patients. Keyword: Classical music therapy, Hallucinations, Schizophrenia